Principles of microwave circuits - Montgomery, C. G. 1909-1950 (Carol Gray).; Dicke, Robert H. (Robert Henry).; Purcell, Edward M. (London, United Kingdom Institution of Engineering and Technology, 1987)
The book reviews developments in the following fields: electromagnetic waves; waveguides as transmission lines; network theory; microwave circuit theorems; waveguide circuit elements; resonant cavities; radial transmission lines; waveguide junctions; mode transformations; and dielectrics in waveguides.
Originally published: New York : McGraw-Hill, 1948.
Electronic reproduction.
Keywords: Microwave circuits; Electronic books